POPULATION AT RISK ESTIMATION DUE TO GROUNDWATER FLUORIDE POLLUTION IN THE FLUOROSIS ENDEMIC AREA OF ASEMBAGUS, EAST JAVA, INDONESIA - Wacano, Dhandhun; Yoneda, Minoru (Universitas Ahmad Dahlan, 2024)
Groundwater is the world's primary source of drinking water. Unfortunately, we face the reality that access to safe drinking water is a worldwide issue nowadays. The presence of fluoride in groundwater is one of the causes of the fluorosis disease, which affects hundreds of millions of people around the world. Asembagus, an endemic area for fluorosis in Indonesia, requires updating its current risk status due to dynamically changing factors over time. Therefore, this research aims to estimate the probability of human health risk based on a population-at-risk calculation. Using an ion-selective electrode, we carefully tested 45 water samples from shallow groundwater in situ. The interpolation technique was used to determine the current potential risk zone and calculate the population at risk. The result showed that the fluoride concentration in the study area varied from 0.29 to 3.41 mg/L, with a mean of 1.22 mg/L. In Asembagus, the threat of skeletal fluorosis still affects 859 people (6.16%), and dental fluorosis affects 1,122 people (8.04%). Based on this study's findings, we concluded that the potential risk of non-carcinogenic fluorosis has significantly decreased since more than 20 years ago. This information is very useful for the government and public health authorities to further mitigate and protect people in the Asembagus area.